Terminology, Ontology and their Implementations Teaching Guide and Notes - Elkin, Peter L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This set of teaching notes provides extensive guidance for educators related to its sister title and contains numerous tools and questions to help educators provide didactics and evaluation of students in this essential area of biomedical informatics. This is needed to understand the central topics of ontology, terminology and terminological systems in healthcare. Twenty-five years ago the notion that ontology would be essential to knowledge representation in healthcare was all but unknown. Almost all important terminologies and many ontologies are now in wide use and are growing in importance. With no general model of what a ontology and terminology should be, there are an increasing number of tools to support ontology / terminology development, implementation and maintenance. Steady progress since then has improved both ontology / terminology content and the technology and processes used to sustain that content. Terminology, Ontology and their Implementations: Teaching Guide and Notes provides extensive teaching materials to accompany Terminology, Ontology and their Implementations . It provides further definition of the topic and explains the use of reference terminologies needed to use them safely. It contains questions and explanations from each section of the textbook, making it easier to use the text in teaching Health Informatics students. The authors also provide supplementary information about the questions, their relevance and their relation to other concepts. This book augments Terminology, Ontology and their Implementations by assisting the understanding of terminology services and the architecture for terminological servers, and consequently serves as an essential tool for educators in their efforts to teach students in their study of health informatics.
Introduction -- History of Terminology and Ontology -- Knowledge Representation and the Logical Basis of Ontology -- Theoretical Foundations of Terminology -- Terminology Requirements and Standards Development -- Terminology Design -- Maintenance -- Quality Control -- Realism Based Ontology -- What is an ontology? -- Ontology vs. terminology -- Ontology vs. taxonomy -- Ontologies and databases -- Ontology and the Semantic Web -- Ontology in biomedical informatics -- Bad ontologies -- The concept orientation -- Why ontologies so often fail -- Recipes for success -- Examples of successful ontologies and of how they are being used -- The place of Referent Tracking in Biomedical Informatics -- Introduction: what is Referent Tracking (RT)? How does it relate to ontology? What does it aim to achieve? Why does it matter? -- Basic principles: how RT is build on top of three important distinctions made in realism-based ontology: particulars types, continuants occurrents, referents references -- Syntax and semantics of RT-expressions -- RT as a development tool for ontologies -- Using RT to detect and prevent flaws in scientific research and ambiguities and inconsistencies in reports and papers -- RT as a solution for semantic interoperability -- Werner Ceusters -- Bioontology in Service of Translational Science -- Introduction to Bioontologies and the OBO Foundry -- The Gene Ontology -- Overview of GO Content and Structure -- GO annotation -- Term Enrichment/Pathway Analysis -- Success Stories -- Challenges -- Bioontologies and Data Annotation Systems -- ImmPort/HIPC -- Kidney Precision Medicine Project -- GEO and Array Express -- Disease and Phenotype Annotation for Translational Studies -- Use of Ontologies at Mouse Genome Informatics -- HPO and the Monarch Project -- Compositionality: An Implementation Guide -- Interface Terminologies -- SNOMED CT -- RxNorm and NDF-RT and ATC codes -- LOINC -- SOLOR -- ICD -- CPT -- HCC Codes / Risk Adjustment and MACRA / MIPS -- DRGs -- NCI EVS -- Nursing Terminologies -- RED / MED -- UMLS Metathesauras and knowledge sources -- Terminological Systems -- HL7 FHIR and APIs -- Lessons Learned and Suggested Research Agenda -- The future of coding and coding systems -- Conclusion.
Keywords: Medical informatics; Bioinformatics; Health Informatics; Health Informatics; Bioinformatics; Terminology as Topic; Medicine; Ontology